Przeobrażenia funkcji wydawniczych polskiego czasopiśmiennictwa misyjnego - Wrzos, Marcin (Annales Missiologici Posnanienses, 2014)
The article deals with the transformation of the editorial strategies of the Polish missionary press. The contents of a missionary magazine, frequency of its publication, the quality of articles etc. depend on the policies of editorial boards and publishers. The goal of the contemporary missionary press is to provide information (missionary news), to influence public opinion, to create correct attitudes towards missions, to inspire different forms of involvement, to educate, to obtain economic support for missions etc. Those who analyze the milieu of the Catholic mass-media underline also its purpose to evangelize. All those aspects are taken into consideration in the article, which analyzes the developments of the Polish missionary press following three periods of recent history: before the Second World War, between 1945 and 2000 and in the 21st century.